Faktor – Faktor Risiko yang Berpengaruh terhadap Kejadian Demam Tifoid pada Orang Dewasa - Arief Rakhman, Rizka Humardewayanti, Dibyo Pramono (Fakultas Kedokteran Universitas Gadjah Mada, 2009)
Background: In 2000 it was estimated that typhoid fever had caused more than 21.6 million morbidity and 216,510 deaths. In Indonesia typhoid fever is still very endemic. Morbidity in semi rural areas reaches 157/ 100,000 in rural population and increases to 810/100,000 in urban population. At District of Bulungan morbidity caused by typhoid fever is still relatively very high. The major cases of typhoid fever of patients hospitalized at RSUD dr. H. Soemarno Sosroatmodjo happen to age group of > 14 years old (63.84%).Objective: To identify risk factors associated with the incidence of typhoid fever in adults.Method: The study was observational and used a case control study design. There were 260 samples, comprising 130 cases and 130 control matched based on age and gender. Location of the study was dr. H. Soemarno Sosroatmodjo Hospital at District of Bulungan, Province of Kalimantan Timur. Cases were hospitalized adult patients diagnosed having typhoid fever based on clinical symptoms and laboratory examination. Control consisted of new patients diagnosed not having typhoid fever. Data analysis used chi square, Odds Ratio (OR) and logistic regression.Result: The result of multivariate analysis showed that only the variable of not washing hands using soap before having meal was associated with the incidence of typhoid fever in adults (p=0.002; OR=1.625; 95%CI=1.497 – 4.602). Whereas the variables of eating out, history of typhoid in the family, availability of clean water and ownership of toilet that did not meet health requirements had no association with the incidence of typhoid fever.Conclusion: The habit of not washing hands using soap before having meal was factor associated with the incidence of typhoid fever in adults at District of Bulungan. Therefore health promotion on clean and healthy lifestyle should be introduced to all community, particularly washing hands using soap before having meal.Keywords: typhoid fever, adults, risk factors, case control